2021
DOI: 10.1177/0890334421991071
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Markers for Breast Hypoplasia in the Early Postpartum Period

Abstract: Background Breast hypoplasia is one reason for insufficient milk supply. Case reports use wide intra-mammary width and certain breast appearances as markers of breast hypoplasia. However, the reliability of these variables has not been determined. Research aims To test the (i) interrater and intrarater reliability of intra-mammary width measurement and interrater reliability of categorizing women’s breasts into breast types, and (ii) feasibility and acceptability of study procedures for the participants. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previously, we devised a survey and diagram depicting breast types to conduct a reliability study and confirmed that researchers could reliably measure women’s intermammary width [ 32 ]. The data collection tool for this current study was designed by adapting items from the survey used in the reliability study [ 32 ], with the addition of several new questions investigating anatomical breast characteristics. The breast type classification (primary outcome) item was based on the breast type diagram devised for the reliability study [ 32 ].…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously, we devised a survey and diagram depicting breast types to conduct a reliability study and confirmed that researchers could reliably measure women’s intermammary width [ 32 ]. The data collection tool for this current study was designed by adapting items from the survey used in the reliability study [ 32 ], with the addition of several new questions investigating anatomical breast characteristics. The breast type classification (primary outcome) item was based on the breast type diagram devised for the reliability study [ 32 ].…”
Section: Methodsmentioning
confidence: 95%
“…The data collection tool for this current study was designed by adapting items from the survey used in the reliability study [ 32 ], with the addition of several new questions investigating anatomical breast characteristics. The breast type classification (primary outcome) item was based on the breast type diagram devised for the reliability study [ 32 ]. All survey questions were piloted with the research team (n = 5), research colleagues (n = 10) and a small group of women who had low milk supply (n = 7) in an iterative manner.…”
Section: Methodsmentioning
confidence: 99%